Guidelines in Gastroenterology: Careful Interpretation Is Essential - Correia,Catarina (2022)
Abstract Introduction: Clinical practice guidelines (CPG) contain recommendations that aim to guide physicians in the diagnosis of and therapeutic approach toward patients affected by gastrointestinal (GI) pathologies. These CPG systematically combine scientific evidence and clinical judgment, culminating in recommendations that have been shown to improve patient care. Material and Methods: European and North American guidelines published in the area of gastroenterology in 2018 and 2019 were considered for inclusion. To standardize the results, only guidelines that used GRADE as an evidence system were included. Thus, in the end, 1,233 recommendations from 29 guidelines published between 2018 and 2019 were analyzed. Results: Of the 1,233 recommendations collected, 324 (26.3%) had a low level of evidence and 127 (10.3%) had a very low level of evidence, indicating little evidence or expert opinion. Of the 29 publications analyzed, 14 (48.3%) did not present any recommendation with a high level of evidence. Regarding the 1,233 individual recommendations expressed in these 29 publications, only 336 (27.25%) assumed a high level of evidence, with 277 (82.44%) referring to liver pathology. Of the recommendations evaluated, 77 were from North American societies and the remaining 1,156 were European recommendations. In relation to the first group, only 3 (3.9%) had a high level of evidence belonging to the Guidelines for Sedation and Anesthesia in GI Endoscopy. Conclusions: More than 25% of all recommendations currently accepted to guide patients with gastroenterological disorders are based on low-quality evidence or expert opinion. Thus, these documents should guide our performance, but clinical sense and multidisciplinarity must not be overlooked in dubious cases and with weak scientific evidence. Research should focus on the development of randomized controlled trials and systematic reviews to improve the evidence supporting the guidelines that guide clinical practice.